Determinan Sisa Lebih Perhitungan Anggaran Desa: Studi Kabupaten Sukoharjo - Melaty, Khoirul Putri; Sari, Shinta Permata (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2021)
The Remainder Village Budget Calculations (SiLPA Desa) is due to the difference between realized budget revenues and expenditures during one budget period. SiLPA DesA describes village financial management  and  the  performance  of  the  Village Governance. This study aims to examine the effect of village original income, village funds, village fund allocations, and the portion of the tax and retribution proceeds on the excess of the village budget calculation. This research uses quantitative research methods. The population in this study  are  150  villages  in  Kabupaten  Sukoharjo.  Based  on the predetermined criteria, a sample of 118 villages are obtained using purposive sampling. The test results use multiple regression analysis   show   that  only  village  original  income  has effect  on the SiLPA Desa, meanwhile village fund, village fund allocation, share of tax and retribution proceeds have no effect on SiLPA Desa.